Household Coping Strategies During the COVID-19 Pandemic in Chile - Palma, Julieta; Araos, Consuelo (Frontiers in Sociology, 2021)
Chile was severely hit by the COVID-19 pandemic. The implementation of social distancing measures strongly affected the Chilean economy: the unemployment rate grew rapidly as well as the proportion of population temporarily excluded from the labour force. This article analyses the strategies deployed by Chilean households to cope with the impact of the pandemic at the intersection with household structure and its socio-economics characteristics. Secondary data analysis from the Encuesta Social COVID-19 (COVID-19 Social Survey), carried out by the Chilean Ministry for Social Development and Families, were used to analyse the income-generating and expenditure-minimising strategies adopted by households during the early months (March to July of 2020) of the pandemic. The results show that 60.3% of households experienced a drop in family income, 70.3% indicated that they had to use at least one income-generating strategy, and 76.6% at least one expenditure-minimising strategy during the early months of the pandemic. Indebtedness and decapitalisation characterised most of the coping strategies adopted by households. While living in multigenerational households does not protect family members from declining economic well-being, older people living in one- and two-generation households were found to be least affected economically during the crisis. They were also less likely to resort to these coping strategies, insofar as their income was mainly secured from pensions. Although female-headed households did not show a greater reduction in income than male-headed households, they were more likely to adopt income-generating strategies. This article draws attention to the possible effects of decapitalisation and indebtedness on the long-term economic well-being of households with different structures, and the resulting inequalities in their capacity to recover from the effects of the pandemic. The findings suggest that having a source of family income that is not dependent on labour market flows is crucial in times of crises.